2005
DOI: 10.1111/j.0022-202x.2005.23779.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Stripping: Determination of the Amount of Topically Applied Substances Penetrated into the Hair Follicles

Abstract: The determination of penetration pathways of topically applied substances into the skin is the subject of several investigations. Recently, follicular penetration has become a major focus of interest. To date, a direct, non-invasive quantification of the amount of topically applied substance penetrated into the follicles had not been possible. The development of such a method was the aim of this study. Therefore, the advantages of both stripping techniques, tape stripping and cyanoacrylate skin surface biopsy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(130 citation statements)
references
References 35 publications
4
123
0
Order By: Relevance
“…26,27 It has been shown that nanoparticles preferentially permeate into the follicles, but not the SC, enabling high accumulation within the follicular reservoir. 17,28 Correspondingly, the comparison of Figures 3c, d -5c, d indicated that larger SLN particles (SLN2 and SLN3) could not penetrate into deep layers of skin even after 6 and 24 h. Only the SLN in the mid-size range (SLN2) could penetrate the upper skin layers (Figure 4b). SLN1 could penetrate into lower skin layers after 24 h (Figure 3d) as depicted by arrows.…”
Section: 25mentioning
confidence: 84%
“…26,27 It has been shown that nanoparticles preferentially permeate into the follicles, but not the SC, enabling high accumulation within the follicular reservoir. 17,28 Correspondingly, the comparison of Figures 3c, d -5c, d indicated that larger SLN particles (SLN2 and SLN3) could not penetrate into deep layers of skin even after 6 and 24 h. Only the SLN in the mid-size range (SLN2) could penetrate the upper skin layers (Figure 4b). SLN1 could penetrate into lower skin layers after 24 h (Figure 3d) as depicted by arrows.…”
Section: 25mentioning
confidence: 84%
“…Follicular uptake of NS, NC, and LNC (in dispersion and in Carbopol HG) on porcine ear skin was assessed quantitatively based on the Differential Stripping method [28]. Depending on the formulation, either 20 µl of the nanoparticle dispersion, or 50 mg of the nanoparticle HG were applied to a predetermined area, followed by a three minute massage or not (depending on experimental setup), and incubated for one hour before starting the stripping process.…”
Section: Follicular Uptake Study Based On the Differential Stripping mentioning
confidence: 99%
“…Therefore, stripping techniques, tape stripping and cyanoacrylate skin surface biopsy have been used to remove the part of the stratum corneum containing dye topically applied [76]. Thus, the "differential stripping" has been shown as a new method that can be used to study the penetration of topically applied substances into the follicular infundibula non-invasively and selectively [20,26,30,76,77]. …”
Section: Routes Of Drug Penetration Through the Skinmentioning
confidence: 99%